2008
DOI: 10.1007/s11595-007-3319-z
|View full text |Cite
|
Sign up to set email alerts
|

Al-Ti-C grain refiner made by ultrasonic levitation

Abstract: An electrostrictive uniaxial ultrasonic levitation reaction system was designed to perform TiC synthesis reaction by suspending graphite powder in Al-3Ti melt and an Al-3Ti-0.15C grain refi ner alloy was obtained. The results show that sound pressure node in which graphite suspends is formed in the melt between radiation block and refl ecting board by ultrasonic and TiAl 3 particles congregate around C powder Meanwhile, due to ultrasonic cavitation, dissolved TiAl 3 provides better surface condition for the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Under the ultrasonic field coupling effect, the incident and reflection sound waves acoustic wave at the Al-Ti/C interface have superimposition effect [11], the high temperature in the melt near the interface Al-Ti/C will produce locally, which can make C a free C atom in Al melt, and also can effectively prevent the formation of Al 4 C 3 directly. The formation of TiC can be expressed by:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the ultrasonic field coupling effect, the incident and reflection sound waves acoustic wave at the Al-Ti/C interface have superimposition effect [11], the high temperature in the melt near the interface Al-Ti/C will produce locally, which can make C a free C atom in Al melt, and also can effectively prevent the formation of Al 4 C 3 directly. The formation of TiC can be expressed by:…”
Section: Resultsmentioning
confidence: 99%
“…The external energy gained from ultrasound make particle release from clusters and distribute dispersedly. Therefore, the effects of acoustic cavitation and acoustic streaming are suitable for the preparation of high performance AlTiC grain refinement [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the rare earth metals have certain refining ability and catalytic effect [11,12], which play an important role in promoting the synthesis of fine TiC particles in the preparation of Al-Ti-C alloy, and thus, Al-Ti-C-RE alloys with better refining efficiency than Al-Ti-C have been developed [13,14,15,16]. Although such alloys have been extensively studied, the refining properties of the prepared Al-Ti-C-RE alloys are not sufficiently stable [17,18]. So far, it has not been widely used in the aluminum and its alloy refining industry.…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature has demonstrated the possibility to join both c-Ti-Al alloys and Ti alloys either to themselves or to other special materials by diffusion bonding. [3][4][5][6][7][8] However, how to improve the DB parameters (bonding time and temperature, etc.) and cut the cost is still a crucial problem.…”
mentioning
confidence: 99%